Resource-Constrained EFL Education in Libya: Teachers’ Classroom Practices and Institutional Challenges - Amnnah Abdulwahab; Arso Setyaji; Wiyaka; Ali Albayyan (JADEs Journal of Academia in English Education, 2026)
Resource limitations remain a major challenge affecting the quality of English as a Foreign Language (EFL) education in many developing countries, including Libya. In under-resourced primary schools, insufficient instructional materials and limited educational facilities may hinder effective English language teaching and learning. This study aimed to explore how resource constraints influence EFL teaching practices and learning processes from teachers’ perspectives. Employing a qualitative case study design, data were collected through semi-structured interviews with English language teachers at a Primary School in Libya during the 2025–2026 academic year. The findings revealed that shortages of modern teaching media, overcrowded classrooms, and limited access to professional development significantly restricted the implementation of communicative language teaching approaches. As a result, teachers relied heavily on traditional rote-learning methods, which reduced student engagement and limited learning outcomes. The study concludes that resource constraints not only affect classroom instruction but also hinder the development of interactive and student-centered EFL learning environments. Therefore, greater institutional support, improved educational infrastructure, and systematic integration of educational technology are needed to enhance the quality and equity of EFL education in Libyan primary schools.